2009
DOI: 10.3892/or_00000450
|View full text |Cite
|
Sign up to set email alerts
|

Small polydispersed circular DNA contains strains of mobile genetic elements and occurs more frequently in permanent cell lines of malignant tumors than in normal lymphocytes

Abstract: Abstract. Small polydispersed circular DNA (spcDNA) belongs to the extrachromosomal pool of DNA and is composed of heterogeneous DNA circles. Whether spcDNA has a special function is currently unclear but their occurrence was suggested to be linked to genetic instability. In this study we investigated as to whether human lymphocytes from healthy volunteers also harbour spcDNA and whether spcDNA is present in all permanent cell lines from human normal and malignant tissues. Moreover, we were interested to see w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…Recombination, replicon misfiring, modified TPRT, and reverse transcription models have been proposed to explain these extrachromosomal DNAs [ 404 407 ]. Their copy numbers are elevated in cancer cells and associated with genome instability [ 408 , 409 ]. Still a poorly studied class of mammalian copy number variants, spcDNAs could conceivably be an additional off-target source of amplicons for some PCR-based analyses of genomic retrotransposon insertions.…”
Section: An Arms Racementioning
confidence: 99%
“…Recombination, replicon misfiring, modified TPRT, and reverse transcription models have been proposed to explain these extrachromosomal DNAs [ 404 407 ]. Their copy numbers are elevated in cancer cells and associated with genome instability [ 408 , 409 ]. Still a poorly studied class of mammalian copy number variants, spcDNAs could conceivably be an additional off-target source of amplicons for some PCR-based analyses of genomic retrotransposon insertions.…”
Section: An Arms Racementioning
confidence: 99%
“…As these mechanisms involve retroviral intermediates, they seem unlikely to explain the formation of LINE circles. A less-specific class of circular DNA, small dispersed circular DNA (spcDNA), has been found to be present in essentially all mammalian cells (70,71). spcDNA consists of heterogeneous circles of sizes from hundreds to thousands of base pairs, and spcDNA is increased in cells with genome instability (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…A less-specific class of circular DNA, small dispersed circular DNA (spcDNA), has been found to be present in essentially all mammalian cells (70,71). spcDNA consists of heterogeneous circles of sizes from hundreds to thousands of base pairs, and spcDNA is increased in cells with genome instability (70,71). spcDNA appears to be derived from chromosomal DNA and contains unique sequence, non-coding sequence and repetitive elements (including Alus and L1s).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the function of spcDNA in telomere regulation might have potential roles in the surveillance of tumor progression. In addition, spcDNA levels are more than 3-fold higher in cancer cells than in normal cells [62] and are further enhanced by treatment with carcinogen [60]. Other reports have shown that the elevated amount of spcDNA is considerably connected with proliferating melanoma cells [63].…”
Section: Spcdnamentioning
confidence: 96%